Fish prey of Weddell seals, Leptonychotes weddellii, at Hope Bay, Antarctic Peninsula, during the late summer - Daneri, Gustavo Adolfo; Negri, Agustina; Coria, Néstor Rubén; Negrete, Javier; Libertelli, Marcela Mónica; Corbalán, A. (Polar Biology)
The study of the feeding habits of Weddell seals, Leptonychotes weddellii, in the area of west Antarctic Peninsula is essential to understand the role they play in the marine food webs, especially considering that this is one of the regions most affected by climate change. With the aim of detecting temporal changes in the fish predation pattern of seals, a total of 217 scats were collected at Hope Bay, during three consecutive summers (2003, 2004 and 2005). The family Nototheniidae comprised over 80% in numbers of fish preyed by seals. The Antarctic silverfish, Pleuragramma antarctica, was, by far, the most frequent and abundant prey species with a mean percentage frequency of occurrence of 48.7% and representing in average 52.1% in numbers of the fish consumed by seals. Other fish species of lesser importance were the nototheniids Trematomus newnesi, Lepidonotothen larseni, Gobionotothen gibberifrons and the channichthyid Chionodraco rastrospinosus. Temporal variation was observed not only in the relative proportions of the different fish prey taxa but also in the sizes of the dominant prey, P. antarctica. Given the high trophic vulnerability of this species to changes in abiotic factors and food web structure and dynamics, a possible influence of El Niño Southern Oscillation events of 2002–2003 and 2004–2005 should not be discarded. Moreover, special attention should be addressed to its population status, distribution and spatial/temporal availability as prey resource of upper trophic level consumers such as L. weddellii which largely depend on P. antarctica. Fil: Daneri, Gustavo Adolfo. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales “Bernardino Rivadavia”; Argentina Fil: Negri, Agustina. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales “Bernardino Rivadavia”; Argentina. Ministerio de ...